2011
DOI: 10.1111/j.1365-313x.2011.04680.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide accumulation in Arabidopsis is independent of NOA1 in the presence of sucrose

Abstract: ). † These authors contributed equally to this work. SUMMARYNitric oxide signals diverse responses in animals and plants. Whereas nitric oxide synthesis mechanisms in animals are well understood, how nitric oxide is synthesized and regulated in plants remains controversial. NOA1 is a circularly permuted GTPase that is important for chloroplast function and is implicated in nitric oxide synthesis. However, the reported consequences of a null mutation in NOA1 are inconsistent. Whereas some studies indicate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
35
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 44 publications
(137 reference statements)
5
35
0
Order By: Relevance
“…Consistent with this earlier report (Van Ree et al, 2011), our results showed that noa1 accumulated reduced levels of Suc compared with the wild-type plants (see Supplemental Figure 16A online). However, this was also the case for ssi2 and ssi2 noa1 plants.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with this earlier report (Van Ree et al, 2011), our results showed that noa1 accumulated reduced levels of Suc compared with the wild-type plants (see Supplemental Figure 16A online). However, this was also the case for ssi2 and ssi2 noa1 plants.…”
Section: Discussionsupporting
confidence: 93%
“…A recent study suggested that the reduced accumulation of NO in the noa1 plants was due to their inability to accumulate the carbon reserve, Suc (Van Ree et al, 2011). Consistent with this earlier report (Van Ree et al, 2011), our results showed that noa1 accumulated reduced levels of Suc compared with the wild-type plants (see Supplemental Figure 16A online).…”
Section: Discussionsupporting
confidence: 92%
“…To further discern the contribution of NR-and L-Argdependent pathways to the HRW-induced responses, we further adopted a genetic approach using Arabidopsis mutants exhibiting null NR activity (nia1/2; Zhao et al, 2009) and indirectly reduced endogenous NO level (noa1; Zhao et al, 2007;Xuan et al, 2010;Van Ree et al, 2011) as well as the triple mutant nia1/2/noa1 impaired in NR-and AtNOA1-dependent NO biosynthesis (Lozano-Juste and León, 2010; Xie et al, 2013). Meanwhile, ABA responses were recorded simultaneously as positive controls.…”
Section: Nr-mediated No Production Is Responsible For Hrw-induced Stomentioning
confidence: 99%
“…To resolve these scientific questions, rbohD, rbohF, nia1/2, nitric oxide associated1 (noa1; Van Ree et al, 2011), nia1/2/noa1, and gork mutants were utilized to investigate the relationship among H 2 , ROS, NO, and GORK in the guard cell signal transduction network. By the combination of pharmacological and biochemical analyses with this genetics-based approach, we provide comprehensive evidence to show that H 2 might be a newly identified bioeffective modulator involved in ABA signaling responsible for drought tolerance, that HRWpromoted stomatal closure was mainly attributed to the modulation of ROS-dependent NO generation, and that GORK might be the downstream target protein of H 2 signaling.…”
mentioning
confidence: 99%
“…However, the function of AtNOS1 as a NOS has recently been questioned (Zemojtel et al, 2006); therefore, the name AtNOS1 has been changed to NITRIC OXIDE ASSOCIATED1 (AtNOA1; Crawford et al, 2006). Recent studies show that AtNOA1 actually has GTPase activity rather than NOS activity (Moreau et al, 2008;Van Ree et al, 2011). However, NOS activity as well as inhibition of NO synthesis by animal NOS inhibitors have been reported in plants (Durner et al, 1998;Corpas et al, 2009).…”
mentioning
confidence: 99%